2018
DOI: 10.1111/aji.12868
|View full text |Cite
|
Sign up to set email alerts
|

Saturated and unsaturated fatty acids differentially regulate in vitro and ex vivo placental antioxidant capacity

Abstract: Our findings suggest that saturated and unsaturated fats differentially regulate placental viability, antioxidant capacity, and inflammation and the actions of gram-positive and gram-negative endotoxins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Further, in Swan71 cells, palmitate decreased cell viability, however oleate (an unsaturated fatty acid) had no effect [50]. The findings from our studies as well as previous studies, suggest that palmitic acid and LA differentially regulate the regulators of cell viability, inflammation and antioxidant capacity [49].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Further, in Swan71 cells, palmitate decreased cell viability, however oleate (an unsaturated fatty acid) had no effect [50]. The findings from our studies as well as previous studies, suggest that palmitic acid and LA differentially regulate the regulators of cell viability, inflammation and antioxidant capacity [49].…”
Section: Discussionsupporting
confidence: 72%
“…The findings from our study, when compared to work undertaken by others, demonstrates that different fatty acids impact divergent pathways in Swan71 cells. For example, palmitic acid, a saturated fatty acid, has been shown to activate a specific pro-inflammatory response through ROS generation [49], increasing IL-6 secretion [29]. Conversely, we show that LA decreased IL-6 secretion.…”
Section: Discussionmentioning
confidence: 46%
“…It was previously suggested that PA stimulates lipid accumulation and oxidative stress in normal mouse hepatocytes, as well as stimulating an inflammatory response through the NOX4 and mitochondrial pathways [31]. Moreover, PA also stimulates oxidative stress responses in βTC6 cells [32], HepG2 cells [33] and HTR-8/SVneo cells [34]. Our study revealed that PA treatment promotes the production of MDA, while decreasing the content of GSH, and reducing the activity of CAT, GSH-PX, SOD, and T-AOC in BEND cells.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, the saturated fatty acids present in this oil could be induced to elevate cell death, reduce total antioxidant capacity, and augment lipid peroxidation. However, it remains unclear how this fatty acid influences collagen behavior (24).…”
Section: Discussionmentioning
confidence: 99%